Development and Validation of the Responsible Drinking Inventory. - Gray, Heather M.; McCullock, Seth P.; Slabczynski, John M.; Siu, Annette M.; LaPlante, Debi A. (Psychological Assessment, 2026)
Responsible drinking is a common term used by a variety of stakeholders. Although many people and organizations discuss responsible drinking, its meaning remains unclear. Researchers have begun to scrutinize the concept, critically questioning its utility, definition, and distinction from other alcohol-related constructs; however, its measurement has remained limited. Accordingly, we present a series of studies describing the development of the Responsible Drinking Inventory (RDI), a new 18-item self-administered measure of responsible drinking beliefs and behaviors. We report upon the creation and the psychometric properties of the RDI across six primary studies. Examinations of the RDI indicated appropriate reliability and validity, including convergent and divergent validity, as well as known groups and predictive validity. The RDI appears to provide information that is consistent with alcohol safety-oriented measures, such as the Protective Behavioral Strategies Scale, and distinct from alcohol harm measures, such as the Alcohol Dependence Scale. The RDI predicts acute consequences of drinking behavior 3 months in the future. This new measure provides unique insights into the nature of responsible drinking and a concise, yet comprehensive way to assess this concept. Public Significance Statement: The Responsible Drinking Inventory is an important new tool for measuring responsible drinking beliefs and behavior. This measure can provide researchers and other stakeholders with the ability to estimate future alcohol-related harms and a clearer understanding of responsible drinking.